The Effect Of Performance-Based Budgeting, Accounting Control And Reporting Systems On Government Performance Accountability - Puan Nazhifa Afronisa; Ni Made Adi Erawati (SEAN Institute, 2024)
Performance accountability is a form of agency accountability for its duties and activities to interested parties or stakeholders. The purpose of this study was to test and analyze the effect of performance-based budgeting, accounting control, and reporting systems on performance accountability of government agencies. The theory used in this research is Agency Theory and Stewardship Theory. The sample used in this study were OPD employees selected using purposive sampling technique with a total of 108 respondents. The data collection method in this study was to use a questionnaire which was then tested and analyzed using multiple linear regression analysis techniques with the SPSS 26 program. The results showed that performance-based budgeting, accounting control, and reporting systems had a positive effect on the performance accountability of government agencies.